2010
DOI: 10.1159/000292648
|View full text |Cite
|
Sign up to set email alerts
|

Organization of a Tumor Bank: The Experience of the National Cancer Institute of Mexico

Abstract: A tumor bank (TB) is an ordered collection of neoplastic samples, normal tissue, and/or fluids preserved under optimal conditions, as well as storing patients’ clinical information. The objective of this article is to outline the planning and logistics necessary for the functioning of the Instituto Nacional de Cancerología (INCan) TB in Mexico City. For the planning and logistics of a TB, several technical, legal, medical, structural, and physical aspects were considered, which can be grouped under four headin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…These analyses provided several relevant and, in part, surprising conclusions. Human tissue for research, especially fresh frozen tissue, is a sparse and rate-limiting resource [14], and therefore adequate use of tissue should and can be enforced via structured project management [12,15,16]. Consequently, most of the effort in general focuses on the acquisition, handling and storage of frozen tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These analyses provided several relevant and, in part, surprising conclusions. Human tissue for research, especially fresh frozen tissue, is a sparse and rate-limiting resource [14], and therefore adequate use of tissue should and can be enforced via structured project management [12,15,16]. Consequently, most of the effort in general focuses on the acquisition, handling and storage of frozen tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Normal tissue was surgically withdrawn from selected areas of normal breast tissue of 31 cancer patients (age from 27 to 89 years, mean 58±17 years) and stored in liquid nitrogen in the INCAN Tumor Bank for 12-24 months (21). Internal control of sample stability revealed that the contents of several proteins (HIF-1α, GLUT, LDH and ATPase) from fresh samples were similar to those stored in the INCAN Tumor Bank (data not shown).…”
Section: Methodsmentioning
confidence: 95%
“…Components of such specimens can be used for DNA, ribonucleic acid (RNA) and protein research. 10 , 11 …”
Section: Methodsmentioning
confidence: 99%